Wireless EV Battery Charge Monitoring With RFID - Chirag C Belegere; Chiranjeev Mishra; Harika P S; Kiran K N (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The presented work introduces an innovative Intelligent Charging Point Management System leveraging IR sensors and Zigbee communication technology. Each charging point is equipped with IR sensors to detect device connections, and the data is transmitted to a central server via Zigbee. On the laptop side, a Python Flask web application offers a user-friendly interface, providing real-time information on available charging slots, locations, and pricing. This integration of hardware and software creates an efficient and responsive system for managing charging points, enhancing the optimization of electronic device charging infrastructure. Users can conveniently access this information through a web browser, facilitating effective planning and utilization of charging resources